Contributions of cocontraction and eccentric activity to stiffness regulation - Silva, P. L.; Fonseca, S. T.; Ocarino, J. M.; Gonçalves, G. P.; Mancini, M. C. (Journal of Motor Behavior, 2009)
Individuals commonly adjust joint stiffness in response to changes in environmental and task demands. The objective of the present study was to evaluate the contribution of muscular cocontraction and eccentric activity to this adjustment. In all, 30 healthy volunteers participated in the present study. The authors indirectly manipulated elbow stiffness by modifying (a) the frequency of forearm movements (frequency conditions) and (b) the kinetic properties of the forearm through the addition of external mass (mass conditions). Multilevel regression models identified muscular cocontraction and eccentric activity as predictors of joint stiffness in the frequency conditions but not in the mass conditions. Results indicated that cocontraction is not the sole mechanism for stiffness regulation. Rather, the mechanisms that different participants used varied as a function of the demands of the task.